Penerapan dan Analisis Hukum Gadai Lahan Pertanian di Desa Gondanglegi Wetan, Kabupaten Malang - Nur Laila Fiskiyatul Jannah; Zainudin Fanani (Department of Islamic Economic Law, Institut Agama Islam (IAI) Al-Qolam, 2019)
This study aims to conduct an analysis related to the application and analysis of agricultural land pawning laws in Gondanglegi Wetan Village, Malang Regency. This research is qualitative using interview method in data collection techniques. The conclusion of this research is that the majority of the community has understood that the pawn transaction of agricultural land is a transaction (contract) that is not justified in Islamic Sharia but in its application the pawn of agricultural land that occurs in Gondanglegi Wetan Village is only based on customary law (adat) which has been applied for generations. On the other hand, there are no provisions regarding regulations or determination of settlement efforts in the event of a breach (breach of contract) in the implementation of pawning agricultural land in Gondanglegi Wetan Village. This is due to the absence of legal force over agricultural land pawning transactions that occur in the community.